Produksi Budaya dalam Seni Grafiti - Wanlie, Wanlie (Masyarakat: Jurnal Sosiologi, 2012)
In the midst of pro’s and con’s on the idea that creative economy (or production of culture) as the new engine of economic growth in a globalized world, what opportunity present for us in a developing country to be able to enter global market as a cultural producer. This paper draws from a case study of Darbotz, an Indonesian graffiti artist, whose works have been entered global market mainly through internet and gave him legitimacy as an influencer among his followers. Technology creates new space and lowers the entry barrier so that the division of sub-arena in the field of cultural production is diminishing. In the arena of cultural production there is a relation of collaboration, not only power relation that enabled actors to maximize their capital. Thus arena and sub-arena become fluid and open for any actors. This is because now eventhough arena of cultural production has its autonormativity rule, logic of capital and comodification also entering the arena. As a result, any actors who can produce distinction in their symbolic goods and exploit their social capital, can enter global market of symbolic goods.